The Idea of Justice in Literature (Wirtschaftsethik in der globalisierten Welt,, 2018)
The theme arises from the legal-academic movement "Law and Literature". This newly developed field should aim at two major goals, first, to investigate the meaning of law in a social context by questioning how the characters appearing in literary works understand and behave themselves to the law (law in literature), and second, to find out a theoretical solution of the methodological question whether and to what extent the legal text can be interpreted objectively in comparison with the question how literary works should be interpreted (law as literature). The subject of justice and injustice has been covered not only in treatises of law and philosophy, but also in many works of literature: On the one hand, poets and writers have been outraged at the social conditions of their time. On the other hand, some of them have also contributed fundamental reflections on the idea of justice itself.Contents The Idea of Justice in Drama.- Narrative Literature, Poetry and Essays.- Graphic Novels and Legal Philosophy Target Groups Lecturers and students of philosophy, economy and literature The Editors Hiroshi Kabashima is professor of jurisprudence in the School of Law at Tohoku University, Japan. Shing-I Liu is professor in the School of Law at National Taipei University, Taiwan. Christoph Luetge is professor of business ethics at Technical University of Munich, Germany. Aurelio de Prada García is professor of philosophy of law at Rey Juan Carlos University in Madrid, Spain.